Affective Polarisation in the Low Countries - Russo, Luana (Politics of the Low Countries, 2025)
Affective polarisation, that is, “view[ing] opposing partisans negatively and copartisans positively” (Iyengar & Westwood, 2015 p. 691), seems to have become a buzzword in field of political behaviour. Since the seminal article of Iyengar et al. (2012), where the concept was delineated for the first time, a plethora of studies engaged with it, making it one of the most popular constructs of the last decade. However, until about four years ago, the study of affective polarisation was primarily a US-centric endeavour. In Europe, affective polarisation has attracted scholarly attention only in about the last four years. This is likely due to the fact that in countries that do not have a two-party system, the feelings of in-group and out-group membership, on which affective polarisation rests, are less immediately visible.